Lithium-rich manganese oxide spinel thin films as 3 V electrode for lithium batteries. (20th October 2015) - Cotte, S.; Pecquenard, B.; Le Cras, F.; Grissa, R.; Martinez, H.; Bourgeois, L.
Abstract: Thin film positive electrodes of lithium-rich manganese oxide spinels were prepared by radiofrequency magnetron sputtering from a LiMn2 O4 ceramic target at a total pressure close to 2 Pa. Post-annealing treatments were necessary to get well-crystallized thin films displaying interesting electrochemical performances. Raman spectrum exhibiting several well-defined bands between 296 and 635 cm −1 is typical for the lithium-rich spinel. Based on ICP, RBS and XRD analyses, the thin films composition is close to Li1.2 Mn1.8 O4 . The latter is also in accordance with a Mn 3+ /Mn 4+ ratio close to 0.1 deduced from XPS measurements. Best electrochemical performance (capacity value, cycling life) between 2 V and 3.5 V vs Li + /Li was obtained for thin films annealed at 600 °C. A volumetric capacity of 52 μAh cm −2  μm −1 (close to about 90% of the theoretical value) was obtained at the first cycle at a C/100 regime. Contrary to most studies carried out on spinel thin films cycled in the 3 V range, no appreciable degradation of the discharge capacity was observed after few tens of cycles at room temperature, highlighting the beneficial effect of substituting 20% of Mn ions by Li ions and the presence of microvoids in thin films that limits the effect of strain generated from volume variation during the Li insertion/deinsertion process.